A CONCEPTUAL REVIEW OF ENGINEERING CONSULTANCY PRACTICE (ECP) BUSINESS MODEL - Lai, Justin; Zin, Rosli; Yahya, Khairulzan (Archives of Business Research, 2014)
The Malaysian government has highlighted liberalization for seventeen (17) service sub-sectors in phases, including architectural and engineering services. Liberalization offers opportunities to transfer of capital, expertise, and technology to domestic firms to expand business. As a result, the local Engineering Consultancy Practices are facing challenges in enhancing their competitiveness in sustain their business in the industry. In a sense, proper business model is one of the main criteria to enhance the business performance. This paper aims to contribute to this overlooked but important research line. Semantically, this paper comprehensively reviews the Engineering Consultancy Practice business model from various aspects and applications. The preliminary finding reveals that the concept of developing new ECP business core values is essential to enhance the existing ECP business performance. Eleven (11) business model core values are introduced in this study, verified through systematic triangulation analysis. The outcome can be used to become a guideline for the engineering consultancy practices in Malaysia.